SME Financing Constraints: Evidence from Survey of Retail Firms in Nepal - Bhandari, Avishek; Kunwar, Nrip Bahandur (Nepalese Journal of Management Science and Research, 2026)
Small and Medium Enterprises have a vital role to play in the development of the economy in Nepal, however, access to formal finance in particular to the retail sector has remained a persistent barrier.Small and Medium Enterprises are of utmost importance for Nepal's economic growth and are contributing to a great extent in job creation, and growth in GDP. However, access to sufficient financing is a significant constraint in the growth of SMEs particularly in the retail sector due to the application of traditional collateral requirements and complicated procedures in lending. This research is focused on the issue of financing constraints of retail SMEs in Nepal and its impact on business operation and growth prospects. Using the quantitative approach, total of 425 retail SME owners were surveyed in major urban centers of Nepal using structured questionnaire as a tool of data collection. Descriptive statistics and multiple regression analysis were used to examine the correlation between financing constraint (collateral requirement, interest rates, processing complexity of loan and information asymmetry) and business performance indicators (revenue growth, operational efficiency and capacity to expand). The results show that collateral requirements (B = -2.143, p < 0.01) and processing complexity of loans (B = -1.892, p < 0.01) have significant impact on the access of SME financing and high interest rate (B = -1.567, p < 0.01) and information asymmetry (B = -1.234, p < 0.01) have also negative impact on the business performance. Among these factors collateral requirements appear to be the most significant barrier reflecting the risk adverse lending practices of the financial institutions. These findings underpin the critical need for policy interventions such as alternative credit assessment mechanism, streamlining of the loan processes as well as targeted financial products for SMEs. The study is relevant to the SME financing literature because it shows some empirical evidence from the retail sector in Nepal, and has implications for policymakers and financial institutions to develop more inclusive financing frameworks.